La percepción de los docentes sobre la deserción escolar en los estudiantes del Pájaro Manaure la Guajira (2024)
The main purpose of this study was to explore teachers' perceptions regarding the causes of school dropout among students at the San Rafael del Pájaro Ethnoeducational Institution, Municipality of Manaure La Guajira. A qualitative study was conducted, grounded in the interpretative paradigm and employing a phenomenological design. Semi-structured interviews were administered to 5 teachers from the ethnoeducational institution. Data analysis involved coding, co-occurrence analysis, and synthesis of categories using semantic networks. It was found that key factors within the school environment related to dropout included emotional support, a safe school environment, lack of support, demotivation, and low academic performance. Regarding family factors, emphasis was placed on parental participation, support, and involvement, alongside issues in family communication.